EPIGENETICS OF CARCINOGENESIS - Rustam N. Mustafin; Elza K. Khusnutdinova (Креативная хирургия и онкология)
Currently, the key mechanisms of carcinogenesis are epigenetic events. Epigenetic factors include DNA methylation, histone modifications, microRNA expression and higher chromatin organization. Non-coding RNAs include microRNAs, small interfering RNAs or siRNAs, piRNAs, long noncoding RNAs or lncRNAs. According to recent data, most of these RNAs are directly formed from mobile genetic elements or have a transposon origin. Non-coding RNAs specifically affect the methylation of the genome and the modification of histones in ontogenesis. This is facilitated by evolutionarily programmed features of activation of transposons, since non-coding RNAs are formed from transposons. Thus, the material basis of epigenetic heredity are the transposons. Stress and aging increase the likelihood of developing cancer. This can be explained by an increase in the number of abnormal activation of mobile genetic elements that are sensitive to stress and hormones. Abnormal activation of transposons in cells leads to genomic instability-most such cells undergo apoptosis. However, in some cases, progressive genomic instability leads to damage to oncospressor genes and oncogenes activation - as a result of apoptosis does not occur, and cells acquire the ability of uncontrolled proliferation with the accumulation of a variety of mutations due to the progressive genomic instability caused by the mobilization of transposons. In each type of malignant tumors, specific cascade mechanisms of activation of mobile genetic elements with the participation of non-coding RNA are triggered. The study of epigenetic mechanisms of development of each type of cancer will enable to develop effective methods for early molecular genetic diagnosis of cancer, as well as targeted therapy at different stages of carcinogenesis.